Prolonged impact of the COVID-19 pandemic on the well-being and roles of family/friend caregivers of older adults living at home in Canadian official language minority or majority communities—Supplementary data file - Savard, Jacinthe; Savard, Sébastien; Duong, Patrick; Hatungimana, Nelly Oriane; Benoît, Josée; de Moissac, Danielle; Dupuis-Blanchard, Suzanne; Robitaille, Annie (Université d'Ottawa | University of Ottawa, 2026)
Résumé: Ce fichier de données supplémentaires a été créé pour compléter un article qui présente les résultats d'une étude qui examinait les impacts à long terme de la pandémie de COVID-19 chez 83 proches aidants de personnes âgées provenant de 4 provinces canadiennes. L'article principal sera publié dans la Revue canadienne du vieillissement. https://doi.org/10.1017/S0714980825100494 Abstract: This supplementary data file was produced to complement an article presenting the result of a study examining the longer-term impacts of the COVID-19 pandemic among 83 unpaid caregivers of older adults from 4 Canadian provinces. The main article will be published in the Canadian Journal on Aging. https://doi.org/10.1017/S0714980825100494
Keywords: pandémie; proches aidants; personnes âgées; fardeau; impact sur la santé perçue; communautés de langue officielle en situation minoritaire; Covid-19 pandemic; caregivers; older adults; burden; impact on perceived health status; official language minority communities